1992
DOI: 10.1001/archsurg.1992.01420120026004
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Follow-up of Breast Carcinoma In Situ in Connecticut

Abstract: Statistics from the Connecticut Tumor Registry from 1979 to 1988 were examined, and individual medical records from 1979 to 1983 were also reviewed. Three hundred nineteen medical records were available for review, documenting 220 cases of ductal carcinoma in situ and 102 cases of lobular carcinoma in situ. In 1979, there were 33 new cases of ductal carcinoma in situ reported to the Connecticut Tumor Registry, representing 1.8% of all breast cancers. There has been a yearly increase in ductal carcinoma in situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…This was Increased occurrence of breast cancer following BCIS has been shown in a number of previous studies from around the world: from Sweden (Wärnberg et al, 2000;Rawal et al, 2005); Switzerland (Franceschi et al, 1998;Levi et al, 2005); The Netherlands (Soerjomataram et al, 2006); and the United State of America (Ward et al, 1992;Habel et al, 1997;Claus et al, 2003). Soerjomataram et al (2006) also found an increased occurrence of skin cancer (SIR 1.7; 95% CI 1.1 -2.6) following BCIS, whereas Ward et al (1992) found that (apart from breast cancer) colorectal, cervical and endometrial cancers were the most prevalent in BCIS patients. On the other hand, Franceschi et al (1998) found no excess risk at any cancer site other than the breast.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This was Increased occurrence of breast cancer following BCIS has been shown in a number of previous studies from around the world: from Sweden (Wärnberg et al, 2000;Rawal et al, 2005); Switzerland (Franceschi et al, 1998;Levi et al, 2005); The Netherlands (Soerjomataram et al, 2006); and the United State of America (Ward et al, 1992;Habel et al, 1997;Claus et al, 2003). Soerjomataram et al (2006) also found an increased occurrence of skin cancer (SIR 1.7; 95% CI 1.1 -2.6) following BCIS, whereas Ward et al (1992) found that (apart from breast cancer) colorectal, cervical and endometrial cancers were the most prevalent in BCIS patients. On the other hand, Franceschi et al (1998) found no excess risk at any cancer site other than the breast.…”
Section: Discussionmentioning
confidence: 55%
“…A number of previous studies have focused on the risk of second breast cancer following a diagnosis of BCIS (Habel et al, 1997;Wärnberg et al, 2000;Claus et al, 2003;Levi et al, 2005;Rawal et al, 2005), with estimates of relative risk generally of the order of two-to fivefold. Few studies have looked at the occurrence of subsequent invasive cancers at other sites (Ward et al, 1992;Franceschi et al, 1998;Soerjomataram et al, 2006), and these were based on relatively small numbers of cases. …”
mentioning
confidence: 99%
“…Cancers of the colorectum, ovarium, lung and skin were some of the most common cancers in women previously diagnosed with an invasive breast cancer (Soerjomataram et al, 2005a). In the USA, colorectal, cervical and endometrial cancer were reported as the most prevalent cancers among BCIS patients (Ward et al, 1992). Thus, we could probably expect an increased incidence of second cancers resembling that of malignant breast cancer within a larger study population and a longer follow-up of BCIS cases.…”
Section: Comparison With Invasive Breast Cancer Cohortmentioning
confidence: 96%
“…radiotherapy) for BCIS (Claus et al, 2003), suggesting a shared aetiology (hereditary or lifestyle) for both first and second cancer. In addition to second breast cancer, other cancers were diagnosed in 17% of DCIS and 3.2% of lobular carcinoma in situ (LCIS) patients (Ward et al, 1992). However, no previous studies assessed the risks of different types of second cancer in BCIS patients.…”
mentioning
confidence: 99%
“…56,57 However, as a practical matter, we encounter local recurrence because of the following points: it is difficult to diagnose preoperatively the extent of lesions, there is some possibility that microinvasive breast cancer exists in the lesions, and the assessment of the margin is unreliable because of the difficulty in distinguishing between noninvasive cancer and atypical ductal hyperplasia.…”
Section: Surgerymentioning
confidence: 99%